2014
DOI: 10.1002/chem.201400129
|View full text |Cite
|
Sign up to set email alerts
|

Host Perturbation in a β‐Hydroquinone Clathrate Studied by Combined X‐ray/Neutron Charge‐Density Analysis: Implications for Molecular Inclusion in Supramolecular Entities

Abstract: X-ray/neutron (X/N) diffraction data measured at very low temperature (15 K) in conjunction with ab initio theoretical calculations were used to model the crystal charge density (CD) of the host-guest complex of hydroquinone (HQ) and acetonitrile. Due to pseudosymmetry, information about the ordering of the acetonitrile molecules within the HQ cavities is present only in almost extinct, very weak diffraction data, which cannot be measured with sufficient accuracy even by using the brightest X-ray and neutron s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 68 publications
1
16
1
Order By: Relevance
“…This wasc onfirmed in the second study of the hydroquinone with acetonitrile included. [94] The acetonitrile molecules order in the cavities and decreaset he symmetry of the structure, but in all cases, they align along the three-fold symmetry axisw ith the electronegative nitrogen reaching furthest into the positive region of the EP as expected from the unperturbed EP.H owever,i tw as shown that the guest molecule polarizes the host structure,w hich leads to as ignificant change in the EP around the host molecule and an increase in the EF by an order of magnitude in the center of the cavity (Figure 8). These changes couldn ot be attributedt ot he changes in geometry of the host, and therefore it was concluded that the mutual electrostatic interactions perturb the electronic structure of the host.…”
Section: Gas Storage and Host-guest Complexesmentioning
confidence: 54%
See 2 more Smart Citations
“…This wasc onfirmed in the second study of the hydroquinone with acetonitrile included. [94] The acetonitrile molecules order in the cavities and decreaset he symmetry of the structure, but in all cases, they align along the three-fold symmetry axisw ith the electronegative nitrogen reaching furthest into the positive region of the EP as expected from the unperturbed EP.H owever,i tw as shown that the guest molecule polarizes the host structure,w hich leads to as ignificant change in the EP around the host molecule and an increase in the EF by an order of magnitude in the center of the cavity (Figure 8). These changes couldn ot be attributedt ot he changes in geometry of the host, and therefore it was concluded that the mutual electrostatic interactions perturb the electronic structure of the host.…”
Section: Gas Storage and Host-guest Complexesmentioning
confidence: 54%
“…In this Review,w eh ave as hown aw ide range of materials problems, where analysis of the ED have gained information beyondt he structure. Important examples that we have described in detail are the analysis of the Zintl concept in thermoelectric materials,w hich is not alwaysv alid as assumed, [31] the ionicity of bondingi ne lemental boron, [39,40] the new emerging class of high pressure electrides, [71][72][73] the mutual electric polarization in host-guest structures, [93][94] andt he magnetic interaction pathways in coordination polymers. [77,79,81,83,84] Thus, there is definitely valuable informationi nt he ED not directly contained in the structure of a material.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inclusion of the larger acetonitrile guest molecule results in a significant change in the host framework, namely, a shorter aaxis (15. host centering of the HQ/MeCN structure (h − k + l ≠ 3n), 37 while the full structure and space group symmetry, P3, was established almost 60 years later by Clausen et al 38 In the latter crystallographic study, the collection of high quality data at both synchrotron and neutron facilities was used in combination with theoretical calculations to model the guest ordering. 38 The study revealed that in any cavity channel all acetonitrile molecules are oriented in the same direction. However, there are three crystallographically different MeCN molecules, and thus cavity channels in the crystal structure and the orientation of MeCN are reversed in one of these three.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Evaluation of the EP was also employed by Clausen et al (2011Clausen et al ( , 2014 in the study of guest-host effects in -hydroquinone frameworks, by the introduction of polar molecules into the cavities of the structure. For the empty framework a feature articles (Left) Experimental electrostatic potential (EP) of C 60 F 18 mapped onto the ED isosurface at = 0.8 e Å À3 .…”
Section: Organic Compoundsmentioning
confidence: 99%